2018
DOI: 10.1111/ejss.12735
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different K:Na ratios in soil on dispersive charge, cation exchange and zeta potential

Abstract: Summary The role of potassium (K) in clay dispersion in agricultural soils containing large concentrations of K could be similar to Na. This research was carried out to assess the effect of potassium to sodium ratios (K:Na) on net dispersive charge, Gapon selectivity coefficient (KG), zeta potential (ζ) and percentage of dispersible clay. Different K:Na ratios at two electrical conductivity levels (EC = 3 and 6 dS m−1) were added to an agricultural loamy soil. The results demonstrated that the net dispersive c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 35 publications
2
5
0
Order By: Relevance
“…With the increase in concentration, the adsorption of exogenous cations is also weakened. Thus, the interfacial interactions of clay particles and cations depend on the concentration of exogenous cations, which is similar to the result of Farahani et al (Farahani et al, 2019). Such issues were further evidenced by the results of the variation in coordination environment and adsorption free energy of mixed cations.…”
Section: Implications For the Interfacial Interactionssupporting
confidence: 85%
See 1 more Smart Citation
“…With the increase in concentration, the adsorption of exogenous cations is also weakened. Thus, the interfacial interactions of clay particles and cations depend on the concentration of exogenous cations, which is similar to the result of Farahani et al (Farahani et al, 2019). Such issues were further evidenced by the results of the variation in coordination environment and adsorption free energy of mixed cations.…”
Section: Implications For the Interfacial Interactionssupporting
confidence: 85%
“…This means that exogenous cations brought in by chemical fertilizers tended to promote the release of intrinsic potassium ions in soils with a high content of illite particles. The competition between mixed cations at the mineral surface has been observed in previous studies (Cheng & Heidari, 2018;de Poel et al, 2017;Döpke et al, 2019;Farahani, Emami, Fotovat, & Khorassani, 2019;Yang et al, 2020). The maximum increase in M + increases as Ca 2+ (10.8) < Na + (14.2) < K + (16.8) < Cs + (19.3), whereas the maximum decrease in K 0+ decreases as Ca 2+ (14.2) > Na + (11.2) > Cs + (9.2) > K + (8.7) (Figure 3).…”
Section: Competition Between Exogenous Cations and Intrinsic Potassiu...supporting
confidence: 55%
“…It is worth noting that existing studies have shown that although the introduction of a positive charge can strengthen the attractive force on soil particles, this force is not stable [ 46 ]. If the particle size of soil aggregates increases, the acting distance will be increased and the acting force will be weakened.…”
Section: Resultsmentioning
confidence: 99%
“…Mean Weight Diameter Geometric Mean Diameter As shown in Table 5, compared with soil treated by original lignin, the MWD of soil treated by aminated lignin increased by 5.88%, and the value of GMD increased slightly by 2.90%. It is worth noting that existing studies have shown that although the introduction of a positive charge can strengthen the attractive force on soil particles, this force is not stable [46]. If the particle size of soil aggregates increases, the acting distance will be increased and the acting force will be weakened.…”
Section: Treatment Methodsmentioning
confidence: 97%
“…Soil aggregate stability is very important for improving the physical, biological and chemical properties of the soil (Nweke and Nnabude, 2015;Zaker and Emami, 2019). The soil structure depends to a great extent on the combination of clay particles with organic matter, this determines physical processes such as the selforganization, absorption, disposal and storage of soil water (Dexter et al, 2008;De-Jonge et al, 2009;Resurreccion et al, 2011;Farahani et al, 2019).…”
Section: Introductionmentioning
confidence: 99%